Evaluation of ec’s authority to tax in view of the principle of legality of taxation - Barlass, T. İrfan (My University, 1999)
With the establishment of the European Community as a supranational organization, it becomes necessary for Member States to relinquish some of their sovereignty rights. Turkey is not yet a member of the European Union. But upon becoming a member she will have to make certain concessions in her constitution with regard to the basic principles of the taxation law - the legality of taxation. Thus being a member Turkey will have to face the conflict between certain parts of her constitution and the European Unions general laws. On my thesis I tried to point the issues that may cause a conflict and then explain how to resolve them. On the first part of my thesis I discussed the institutional structure of the European Unions and its legislative instruments. Although these are not directly related to my subject of study, I started with them because without knowing them it would not be possible to understand the issues discussed in the following parts. The second part of my thesis is about the right to tax. This part is in two sections. In the first section I discussed the historical background of some of the Member States' right to tax. In second section I tried to explain the European Union's right to tax concept to-day; and also mentioned some of the tax provisions in the treaties. However, by mentioning these provisions my intention was not to explain every single tax in detail, but to bring out clearly the European Unions authority to tax. Part three is about the meaning of the principle of the legality of taxation, its dimensions and sub-dimensions its exceptions and its place in the Turkish constitution. Finally in part four I pointed out the provisions of the Turkish constitution which will cause a conflict about the right to tax with the European Union's authority to tax and the supremacy of the EU-law. For this part I studied how certain Member States made changes in their constitutions to comply with the European Union's general rules.
Keywords: AVRUPA EKONOMİK TOPLULUĞU-PARA DEĞİŞİMİ; Döviz; Ekonomi; Finansman ekonomisi; Para